Penyalahgunaan Paksaan sebagai Dasar Pembatalan Perjanjian - Syamsul Arifin; Sumriyah (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The agreement in the formation of the agreement should be a unanimous agreement and a favorable agreement. The Civil Code governs the legal provisions of the agreement, the legal terms of the agreement, the result of an agreement and the interpretation of the agreement. The civil law/common low legal system has different main rules regarding duress (dwang/duress). Coercion can be absolute (absolute) and relative coercion. Absolute coercion means that the subject of the agreement in this case is placed in a position of no other choice or placed in a position of having to accept the agreement. While relative coercion still provides an opportunity for one who is forced to consider accepting or rejecting the agreement. A threat can occur or be carried out using legal or illegal means or means. In this study, we try to analyze the validity of agreements and legal consequences of agreements containing coercion (dwang/duress) according to the civil law system (Indonesian Civil Code) in treaties.